(untitled) (Development Service Industry Management, 2025)
The article explores the theoretical, methodological and applied aspects of implementing the principles of sustainable development and circular economy in the agricultural sector of the Ukrainian economy. The relevance of the topic in the context of global challenges is substantiated, in particular, the growing shortage of natural resources, climate change, land degradation, energy crisis, as well as in conditions of military operations, which increase the need for effective management of the resource potential of agricultural enterprises. The conceptual principles of the circular economy as a new paradigm of economic growth, which is based on the principles of resource reuse, waste reduction and environmental responsibility, are considered. The focus of the study is the formation of a systemic approach to resource circulation in agribusiness, which involves the integration of labor, land, capital, technological, information and financial resources into closed production and economic cycles. The author proposes a new interpretation of the concept of “resource circulation in agribusiness” as a complex process that encompasses not only production and processing, but also logistics, storage, reuse and processing of residual resources. The author’s model of resource circularity is presented, which takes into account regional characteristics, infrastructure capabilities and the level of innovative development of agricultural enterprises.Particular attention is paid to the analysis of barriers that hinder the implementation of circular approaches in agricultural production in Ukraine. In particular, a number of systemic problems have been identified: imperfect regulatory framework, insufficient state support for sustainable initiatives, limited access to investments and innovations, weak development of rural infrastructure and low level of environmental awareness of business entities. An assessment of the resource potential of the agricultural sector has been carried out, taking into account qualitative and quantitative characteristics, and directions for increasing the efficiency of its use based on the implementation of the principles of eco-efficiency, resource conservation, bioeconomy and digital technologies have been identified.